2020
DOI: 10.1111/bjh.16750
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation in children with hereditary spherocytosis

Abstract: Summary Hereditary spherocytosis (HS) is a common inherited haemolytic anaemia attributed to disturbances in five different red cell membrane proteins. We performed a retrospective study of 166 children with HS and describe the clinical phenotype according to the genotype. In 160/166 (97%) children with HS a disease‐causing mutation was identified. Pathogenic variants in ANK1, SPTB, SLC4A1 and SPTA1 were found in 49%, 33%, 13% and 5% of patients. Children with SLC4A1‐HS had the mildest phenotype, showing the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 21 publications
7
59
0
1
Order By: Relevance
“…We found no significant difference for any indices between patients carrying ANK1 or SPTB variants. Our data were similar to the those reported in a study by Aggarwal et al (2019) and Tole et al (2020) , where they found that the indices in patients with ANK1 variants were similar to the SPTB group. Moreover, Tole et al (2020) found that the variant type or location within each gene did not predict the disease severity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found no significant difference for any indices between patients carrying ANK1 or SPTB variants. Our data were similar to the those reported in a study by Aggarwal et al (2019) and Tole et al (2020) , where they found that the indices in patients with ANK1 variants were similar to the SPTB group. Moreover, Tole et al (2020) found that the variant type or location within each gene did not predict the disease severity.…”
Section: Discussionsupporting
confidence: 92%
“…Our data were similar to the those reported in a study by Aggarwal et al (2019) and Tole et al (2020) , where they found that the indices in patients with ANK1 variants were similar to the SPTB group. Moreover, Tole et al (2020) found that the variant type or location within each gene did not predict the disease severity. Here, ANK1 death domain variants were associated with lower levels of MCV and MCH compared to other ANK1 domains, but the number of patients was limited.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The αand β-spectrin protein heterodimers self-aggregate in a head-to-head manner to form tetramers that bind to the lipid membrane via ankyrin, protein 4.2, and band 3 [16]. Tole et al [17] showed that children with autosomal recessive SPTA1-HS had the most severe clinical phenotype with almost all patients requiring splenectomy in early childhood. Consistent with their findings, the proband with severe clinical manifestations in this study had the novel compound heterozygous mutations, c.83G > A and c.190G > A of the SPTA1 gene, and these were respectively inherited from an asymptomatic mother and father.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of HS include anemia, jaundice and splenomegaly. Most of the neonates with HS present with jaundice at the early stages of the disease, which then progresses into severe anemia (1). For the neonates with HS aged <1 year, the clinical manifestations are usually severe, with the majority of patients showing initial jaundice and subsequent severe anemia.…”
Section: Introductionmentioning
confidence: 99%